2003
DOI: 10.1093/annonc/mdg287
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of vincristine, doxorubicin and dexamethasone (VAD) administered as intravenous bolus injection and VAD with liposomal doxorubicin as first-line treatment in multiple myeloma

Abstract: Our multicenter trial, which included an unselected patient population, indicated that both VAD bolus and VAD doxil can be administered to outpatients and can provide an equal opportunity of rapid response in many patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 16 publications
4
36
0
Order By: Relevance
“…A number of preliminary studies have evaluated the incorporation of pegylated liposomal doxorubicin into VAD regimens [16][17][18][19]. Overall, these studies demonstrated that this regimen had activity in newly diagnosed or relapsed/refractory multiple myeloma patients who had an acceptable tolerability profile [16][17][18][19].…”
Section: Pegylated Liposomal Doxorubicinmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of preliminary studies have evaluated the incorporation of pegylated liposomal doxorubicin into VAD regimens [16][17][18][19]. Overall, these studies demonstrated that this regimen had activity in newly diagnosed or relapsed/refractory multiple myeloma patients who had an acceptable tolerability profile [16][17][18][19].…”
Section: Pegylated Liposomal Doxorubicinmentioning
confidence: 99%
“…Overall, these studies demonstrated that this regimen had activity in newly diagnosed or relapsed/refractory multiple myeloma patients who had an acceptable tolerability profile [16][17][18][19]. These studies, which used a dose and schedule of dexamethasone similar to those of the VAD regimen, have 40 Modifications to Therapy for Multiple Myeloma suggested that pegylated liposomal doxorubicin is an acceptable alternative to conventional doxorubicin in combination chemotherapy regimens for the treatment of multiple myeloma.…”
Section: Pegylated Liposomal Doxorubicinmentioning
confidence: 99%
See 3 more Smart Citations